The Influence of Health Development on the Quality of Human Resources in the City of Bandung - Kurniati, P S; Nisa, T K; Amin, M SAl (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Health is an important aspect that supports the successful development of an area. With healthy human resources, the implementation of development will be more effective towards success. Every country or region must have a place that can support the health of its people properly and well, therefore health development towards a better direction is very necessary in an area. The purpose of this study is to form awareness of the importance of health development in the community in order to support other developments. The method used is a descriptive qualitative research method using literature studies. This research show that health development is very influential on the quality of human resources. Therefore, the government must be able to minimize obstacles to health development by improving the economy of the community to improve the quality of health and human resources.